Life Cycle Impact Assessment Priok Power Generation Unit: Comparison Based on Operating Time Span - Wicaksono, Adam; Prayitno, Heru Pujo; Prabowo, Himawan Khalid (Department of Mechanical and Industrial Engineering, 2025)
Priok Power Generation Unit (PGU) is a combined cycle power plant (CCPP) which is one of the national vital objects with a generating capacity of 2,723 MW which functions as a load follower and Peaker in the electricity network system. This study aims to look at the environmental impact performance resulting from plant operating patterns January-December in 2020 and 2022, which was carried out using the life cycle assessment (LCA) method with SimaPro. The method life cycle impact assessment uses the ReCipe and CML IA baseline methods. The purpose of this comparison is to see improvements in the environmental performance of generating units to support sustainability. The results of this study show that there has been a change in the results of the environmental impact assessment in the Green House Gases (GHG) and Land Use Change (LUC) are the impact categories with the most significant reduction, namely more than 90%. Meanwhile, water footprints are the only impact that experiences an increase in environmental impacts during the 2020 operating period compared to the 2022 operating period.